Algal biorefinery: An integrated approach for sustainable biodiesel production. (December 2019) - Kumar, Dipesh; Singh, Bhaskar
Abstract: Numerous studies on the techno-economic and life cycle assessment of microalgal biodiesel production are available in the literature, and an overwhelming majority of such studies suggest that the standalone production of biodiesel is currently unviable. The production of microalgal biomass using the currently available technologies costs approximately $4.92 kg −1, which is unacceptably high for biodiesel production. The challenges lie in high biomass production cost and unfavorable energetic balance and significant process, and engineering advancements are desirable before mass-scale production of algal oil and biodiesel at a cost-competitive price is realized. On the other hand, various high-value products sourced from microalgae are already commercialized. The biomass production cost of $4.92 kg −1 is more than acceptable if such products are also derived which, according to some estimates, may command a price as high as $123 kg −1 biomass. It is expected that with process modifications and engineering advancements, the biomass production cost can be brought down to as low as $0.50 kg −1 . Moreover, coupling phycoremediation of pollution loads in waste streams to microalgal biomass production offers economic (up to $170 t −1 biomass produced) and environmental gains (90% reduction in water footprint, improved GHG balance, and a substantial reduction in external input of fertilizers). Such approaches are more likely to translate into an economically appealing and environmentally desirable business model. The current study is an attempt to analyze some of the recent research investigations addressing the concept of a microalgal biorefinery for the production of biodiesel. Highlights: Biodiesel is one of the most popular choices of biofuel. Standalone production of algal biodiesel is not viable. Processing of biomass in a biorefinery holds tremendous promise. Coupling algae cultivation to wastewater treatment is appealing. Significant progress has been achieved in realizing an attractive algal-biorefinery.